2021
DOI: 10.1007/s11060-021-03798-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Proton therapy for adult medulloblastoma: Acute toxicity and disease control outcomes

Abstract: The first author's name was incorrectly spelled in the initial online publication.The original article has been corrected.Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…It is noteworthy that at 2 years, the reported actuarial freedom from G ≥ 3 toxicity was greater than 90% (Figure 2). These data compares favorably with previous studies [3][4][5][6][7][8]16 and supports the safety and efficacy of proton CSI for the control of CNS tumors.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…It is noteworthy that at 2 years, the reported actuarial freedom from G ≥ 3 toxicity was greater than 90% (Figure 2). These data compares favorably with previous studies [3][4][5][6][7][8]16 and supports the safety and efficacy of proton CSI for the control of CNS tumors.…”
Section: Discussionsupporting
confidence: 83%
“…Liu et al reported 4-year LC and DFS of a cohort of 15 AYAs with medulloblastoma of 90% and 90%, respectively. 8 Importantly, LC, DC, and OS were 100% among AYAs in our cohort. Due to the small numbers, the difference of these outcome-metrics was not statistically different when compared to children (Table 2).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations